Enforcement of Corporate Criminal Offense Against Transfer Pricing Abuse Modus Operandi - Hotlan Wanto Siahaan; Yasmirah Mandasari Saragih (Badan Penerbit STIEPARI Press, 2024)
Transfer pricing is the practice of fixing transaction prices between companies that have special relationships within a business group. In the context of the global economy, this practice is often abused by multinational corporations as a mode of tax avoidance, namely by shifting profits to countries with lower tax rates (tax havens). Transfer pricing abuse not only harms state revenues, but also creates unfair business competition. Law enforcement against corporate crime in this case faces various challenges, especially in proving malicious intent (mens rea) and identifying the criminal responsibility of corporate entities. This research aims to identify the modus operandi often used in transfer pricing abuse and analyze the law enforcement strategies that have been implemented in Indonesia. The research methods used are normative and empirical juridical with a qualitative approach. The results show that the common modus operandi includes manipulation of sale/purchase price, use of shell companies, and fictitious contracts. An effective law enforcement strategy requires inter-agency collaboration and firmer regulations regarding corporate criminal liability. Therefore, strengthening the tax audit system and increasing the capacity of law enforcement officers are needed to prevent and crack down on transfer pricing abuse.